TECHNOLOGY IN EDUCATION ELECTRONICS-DIDACTIC OCCUPATION MEANS WITHOUT APPLYING THE EFFECTIVENESS OF THE ORGANIZATION (Archive of Conferences, 2021)
In this paper, the process of technology education in secondary schools in general the fact that the use of electronic-didactic tools and the use of modern information technologies are one of the most important tasks in the preparation of students for technology, and the formation of students as a free-thinking, independent, creative person, is given information